Health and Social Care Systems of the Future: Demographic Changes, Digital Age and Human Factors Proceedings of the Healthcare Ergonomics and Patient Safety, HEPS, 3-5 July, 2019 Lisbon, Portugal - Cotrim, Teresa Patrone; Serranheira, Florentino; Sousa, Paulo; Hignett, Sue; Albolino, Sara; Tartaglia, Riccardo (Advances in Intelligent Systems and Computing, 2019)
This book discusses how digital technology and demographic changes are transforming the patient experience, services, provision, and planning of health and social care. It presents innovative ergonomics research and human factors approaches to improving safety, working conditions and quality of life for both patients and healthcare workers. Personalized medicine, mobile and wearable technologies, and the greater availability of health data are discussed, together with challenges and evidence-based practice. Based on the Healthcare Ergonomics and Patient Safety conference, HEPS2019, held on July 3-5, 2019, in Lisbon, Portugal, this book offers a timely resource for graduate students and researchers, as well as for healthcare professionals managing service provision, planners and designers for healthcare buildings and environments, and international healthcare organizations.